Efficacy and Safety of Docetaxel and Sodium Cantharidinate Combination vs. Either Agent Alone as Second-Line Treatment for Advanced/Metastatic NSCLC With Wild-Type or Unknown EGFR Status: An Open-Label, Randomized Controlled, Prospective, Multi-Center Phase III Trial (Cando-L1) - Wu, Lin; Deng, Chao; Zhang, Hui; Weng, Jie; Wu, You h.; Zeng, Shan; Tang, Tie g.; Cao, Pei g.; Qiu, Bo; Zhang, Li; Duan, Hua x.; Zhang, Bing; et al. (Frontiers in Oncology, 2021)
Second-line treatment options for advanced/metastatic non-small cell lung cancer (NSCLC) patients are limited. We aimed to evaluate the efficacy and safety of docetaxel/sodium cantharidinate combination vs. either agent alone as second-line treatment for advanced/metastatic NSCLC patients with wild-type or unknown EGFR status. A randomized, open-label, phase III study was performed at 12 institutions. Patients with failure of first-line platinum regimens were randomized to receive either single-agent sodium cantharidinate (SCA) or single-agent docetaxel (DOX) or docetaxel/sodium cantharidinate combination (CON). The primary endpoints were centrally confirmed progression-free survival (PFS) and overall survival (OS). The secondary endpoints were objective response rate (ORR), disease control rate (DCR), quality of life (QoL) and toxicity. A total of 148 patients were enrolled in our study between October 2016 and March 2020. After a median follow-up time of 8.02 months, no significant difference was observed among the three groups in ORR (SCA vs. DOX vs. CON: 6.00% vs. 8.33% vs. 10.00%, respectively; p=0.814) and DCR (74.00% vs. 52.00% vs. 62.50%, respectively; p=0.080). In additional, the mOS was significantly higher in the CON group, compared with the single-agent groups (7.27 vs. 5.03 vs. 9.83 months, respectively; p=0.035), while no significant differences were observed in terms of PFS (2.7 vs. 2.9 vs. 3.1 months, respectively; p=0.740). There was no significant difference in the baseline QoL scores between the three groups (p>0.05); after treatment, life quality in SCA and CON group was significantly better than that in the DOX group (p<0.05). Furthermore, the incidence of adverse events (AEs) in the SCA group was significantly lower (46.00 vs. 79.17 vs. 25.00%, respectively; p=0.038) and the incidence of grade ≥3 AEs was also significantly lower in the SCA group compared with the DOX and CON groups (10.00 vs. 82.00 vs. 30.00%, respectively; p=0.042). Single-agent SCA and single-agent DOX has similar therapeutic efficacy in the second-line treatment of advanced/metastatic NSCLC with wild-type or unknown EGFR status, but single-agent SCA has fewer AEs and better QoL. Also, SCA plus DOX can significantly improve OS and exerted a significant synergistic effect, with good safety and tolerance profile.